KESELARASAN PENDIDIKAN SAINS DI SEKOLAH DAN DI RUMAH - Yudiyanto, Yudiyanto (JURNAL TARBAWIYAH, 2014)
Science education for children is expected to deliver the basic thinking abilities and life skills. Science education for elementary school is demanded based on the characteristics of thinking their ages. Teaching science needs harmony between teaching at school and at home. Teaching science at home and neighborhood should be conducted with respect to the development of the childs age and suitability of school subjects. Understanding each parents will be very important to a childs development as a basic in learning of science at home and neighborhood. Warmth in helping children respond to any scientific phenomena at home and the neighborhood will be very beneficial to children in learning science at home and the neighborhood as a continuation of the process of science teaching in schools